The CRC handbook of mechanical engineering - Kreith, Frank; Goswami, D. Yogi (Mechanical engineering handbook series., 2005)
Since the first edition of this comprehensive handbook was published ten years ago, many changes have taken place in engineering and related technologies. Now, this best-selling reference has been updated for the 21st century, providing complete coverage of classic engineering issues as well as groundbreaking new subject areas. The second edition of The CRC Handbook of Mechanical Engineering covers every important aspect of the subject in a single volume. It continues the mission of the first edition in providing the practicing engineer in industry, government, and academia with relev.